Photographing Community Sports in Public Spaces: A Sports Law Perspective - Siahaan, Derry Renanda Putra; Yasmine, Mayesha Andriana (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
The increasing practice of photographing individuals engaged in community sports activities in public spaces has raised legal concerns in the context of privacy and personal data protection. Community sports, such as running or exercising in public open spaces, are non-commercial activities aimed at health, fitness, and social participation. Nevertheless, photographs taken without the consent of the individuals depicted and later processed or commercialized through digital platforms create potential legal violations. This study examines the legality of such practices from the perspective of Indonesian sports law and related legal frameworks. Using a normative juridical method with statutory and conceptual approaches, this research analyzes Law Number 11 of 2022 on Sports, Law Number 27 of 2022 on Personal Data Protection, the Electronic Information and Transactions Law, and the Copyright Law. The study finds that participation in community sports within public spaces does not constitute implied consent to the capture, processing, or commercial use of personal images. Facial images are classified as personal data and require explicit consent. Furthermore, copyright protection of photographs does not override the personality rights of the individuals portrayed. Accordingly, stronger legal safeguards are necessary to protect individual rights while preserving the social function of public spaces and community sports.